Effect of palm kernel shell (PKS) powder on cure characteristic, physical and mechanical properties of acrylonitrile rubber (NBR) composites / Nor Adabiah Md Nayan - Md Nayan, Nor Adabiah (2020)
In this research, Palm Kernel Shell (PKS) was used in NBR composite to evaluate the strength of PKS as potential filler in the NBR composites. However, there some problem due to the polarity of the filler and the rubber matrix that was effect the physical and mechanical properties of the PKS filled NBR composites. The effect of palm kernel shell (PKS) powder on cure characteristics, physical and mechanical properties of acrylonitrile rubber (NBR) composites was successfully investigated. Palm kernel shell filled Nitrile Rubber by the different formulation (0 phr, 5 phr, 10 phr, 15 phr and 20 phr) were compound br two roll mill machine. Cure characterization was done by Moving Die Rheometer. By testing the cure characterization of the filler, scorch time and cure time can be obtained. The tensile strength, elongation at break and crosslink density shows decrement trend while the Young’s modulus and hardness demonstrates increment trend as filler loading increase. Tensile strength was decrease as the filler loading increase is due to poor adhesion between the filler and rubber matrix. while elongation at break was reduce due to effect of stiffening and hardening. From this research, 10 phr of PKS powder was concluded as optimum loading. As it shows the highest tensile strength compared to other loading.